Gaya Kepemimpinan Distributif Kepala Sekolah dalam Upaya Meningkatkan Nilai Kesadaran Diri Siswa tentang Deep Learning di MI Muhammadiyah 11 Secinde - Hardiyanti, Nungki Restuningtyas; Sulton, Sulton (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
This study aims to determine whether the ditributional leadership style possessed by the principal is able to provide positive efforts in fostering students' self-awareness values to face changes in the deep learning curriculum at MI Muhammadiyah 11 Secinde. The research, which was carried out using a qualitative descriptive method with fenomenology sistem by prioritizing direct observation and interviews as its main instruments, was able to describe the school's problems with limited infrastructure and technological accessibility, making the work of the school community double in supporting the increasingly developing curriculum change pattern. This has quite an impact on the readiness of the school community in the learning process, but the principal is able to motivate all of his community so that learning at MI Muhammadiyah 11 Secinde can run smoothly.